ANALISIS KESALAHAN SISWA KELAS VII DALAM MENYELESAIKAN SOAL TES PEMAHAMAN KONSEP MATEMATIS PADA MATERI PECAHAN - Satriawan, Alfrianus; Syrifah Fadillah; Utin Desy Susiaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by students' difficulty in understanding how to convert mixed fractions into improper fractions, which is a misconception in understanding the concept. This study aims to analyze students' errors in solving fraction problems based on their mathematical understanding and the influencing factors. The research employs a qualitative method with a descriptive approach. The study was conducted at in the 2025/2026 academic year. Data were collected through written tests, interviews, and documentation, and then analyzed through data reduction, data presentation, and drawing conclusions. Based on the research results, errors in solving fraction problems are errors in understanding concepts (K1) with a percentage of 40%, calculation errors (K2) contributing only 5% of the total errors, and unidentified answer errors (K3) at 7.5%. This research shows that students' success in solving fraction problems is greatly influenced by conceptual understanding.